Coût énergétique de la course en montée et en descente chez les coureurs entraînés pour la course de montagne - Praz, C.; Jagdeep, S.; Praz, M.; Dériaz, O. (Schweizerische Zeitschrift für Sportmedizin und Sporttraumatologie, 2011)
Running performance is mainly influenced by the maximum oxygen consumption (VO2max), the VO2max fraction that can be maintained during a given exercise duration and the energetic cost. Between elite runners, the greatest interindividual differences are observed for this last parameter. For some of these runners, it would be a great optimization potential. Many factors influence the energetic cost of running. We have tried to know if the training run profile has an influence on the cost. We compared 2 groups of runners: a group of fell runners (n =10) and a group of road or track runners (n = 10). Treadmill tests horizontal, uphill and slighty downhill with indirect calorimetry, anthropometric measurements, were performed to characterize the 2 groups. Energetic cost was determined with the measure of oxygen consumption. When they ran horizontally, fell runners were more economical with low running speed but the difference between the 2 groups became narrower when they accelerated, and finally there was no difference any more at higher running speeds. For down- and uphill running the efficiency against gravity of the fell runners was greater but again only for very low speed. So it appears that a fell running training brings some energetic improvement that allows to run faster with the same energy expenditure for slow running speed.